METHODS FOR DEVELOPING LABOR ACTIVITY SKILLS IN STUDENTS (Web of Teachers: Inderscience Research, 2026)
The development of labor activity among students is one of the key objectives of modern education systems, as it directly influences students’ professional readiness, social adaptation, and economic independence. In the context of globalization and rapid technological progress, higher education institutions are required not only to provide theoretical knowledge but also to cultivate students’ practical skills, work ethics, and motivation for labor activity. This article aims to analyze effective methods for developing labor activity among students based on pedagogical, psychological, and socio-economic approaches. The research employs qualitative and analytical methods, including literature review, comparative analysis, and pedagogical observation. The results demonstrate that integrating practical training, project-based learning, career-oriented education, and motivational strategies significantly enhances students’ labor activity. The findings of the study contribute to improving educational practices and offer practical recommendations for educators and policymakers.